1971
DOI: 10.1038/bjc.1971.38
|View full text |Cite
|
Sign up to set email alerts
|

The Variability of Individual Tolerance to Methotrexate in Cancer Patients

Abstract: Individual tolerance to single or widely spaced doses of methotrexate was explored in 49 patients with advanced cancer with normal serum creatinine and/or blood urea nitrogen. Methotrexate was given as an intravenous infusion over 1 hour at initial doses of 80-120 mg./m 2 body surface area. The doses were increased by 50% increments every 2 weeks until moderate toxicity occurred, arbitrarily defined as leukopenia <5000/mm. 3 , and/or thrombocytopenia <100,000/mm. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

1975
1975
1994
1994

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(13 citation statements)
references
References 12 publications
0
12
0
1
Order By: Relevance
“…These include malignant infiltration, tissue necrosis secondary to vascular occlusion, anti-metabolite effects of chemotherapy or radiotherapy and infective agents (Hansen et al, 1971;Wray et al, 1980;Rand et al, 1982). The diversity of micro-organisms isolated has generated considerable debate as to their significance.…”
mentioning
confidence: 99%
“…These include malignant infiltration, tissue necrosis secondary to vascular occlusion, anti-metabolite effects of chemotherapy or radiotherapy and infective agents (Hansen et al, 1971;Wray et al, 1980;Rand et al, 1982). The diversity of micro-organisms isolated has generated considerable debate as to their significance.…”
mentioning
confidence: 99%
“…Previous reports have shown such a dose to be safe when given by intra venous push [33,34]. Tumor shrinkage with this schedule was rapid and correlated well with subjective relief from pain or trismus.…”
Section: Discussionmentioning
confidence: 60%
“…There are physiologic changes which affect metabolism and turnover of anticancer drugs in the elderly [17][18][19], A study done by Hansen et al [20] indicated an increased susceptibility in the elderly to hematologic toxicity induced by methotrexate. The reduction in renal func tion may explain the adverse effect of metho trexate in the elderly [21].…”
Section: Discussionmentioning
confidence: 99%